Continuous monitoring of kNN queries in wireless sensor networks - YAO, Yuxia (Institutional Knowledge at Singapore Management University, 2006)
Wireless sensor networks have been widely used for civilian and military applications, such as environmental monitoring and vehicle tracking. In these applications, continuous query processing is often required and their efficient evaluation is a critical requirement to be met. Due to the limited power supply for sensor nodes, energy efficiency is a major performance measure in such query evaluation. In this paper, we focus on continuous kNN query processing. We observe that the centralized data storage and monitoring schemes do not favor energy efficiency. We therefore propose a localized scheme to monitor long running nearest neighbor queries in sensor networks. The key idea is to establish a monitoring area for each query so that only the updates relevant to the query are collected. Experimental results show that our scheme outperforms the centralized scheme in terms of energy efficiency and network lifetime.